Knowledge, Attitudes, and Clinical Intentions of Dental Students Toward Botulinum Toxin Use: A Cross-Sectional Study - Esra Bilgi - Ozyetim; Merve Dede (Clinical Dentistry and Research, 2026)
Background and Aim: Botulinum neurotoxin (BoNT) hasgained increasing importance in dental practice for boththerapeutic and aesthetic applications. However, its safe andeffective use requires adequate knowledge and training. Thisstudy aimed to evaluate the knowledge, attitudes, and clinicalintentions regarding the use of BoNT among dental students.Materials and Methods: This cross-sectional study wasconducted using an online, self-administered questionnairedistributed to dental students at two foundation universities inTurkey. The questionnaire assessed demographic characteristics,knowledge of BoNT (definition, indications, contraindications, andadverse effects), and attitudes toward its clinical use. Data wereanalyzed using descriptive statistics and Chi-square tests, withstatistical significance set at p < 0.05.Results: A total of 506 students participated. Only 34.4%of students correctly identified BoNT as a toxin, and 18.6%correctly identified all clinical indications of BoNT. Knowledgeregarding contraindications was particularly limited, withonly 2.8% answering correctly. Despite these gaps, 76.7%of students reported willingness to use BoNT in clinicalpractice, and 77.1% expressed interest in attending trainingcourses. Students who expressed willingness to undergoBoNT injections themselves were significantly more likely toreport willingness to administer BoNT clinically (p < 0.05). Noconsistent increase in knowledge levels was observed acrossacademic years.Conclusion: Dental students demonstrated limited knowledge ofBoNT despite a high level of interest in its potential clinical use. Thesefindings provide preliminary information regarding undergraduatedental students’ awareness and perceptions of BoNT.